Manajemen Penerimaan Peserta Didik Baru Jalur Prestasi di SMA Negeri 1 Parigi Kabupaten Pangandaran - Dede Ulfah Munirah Aziz; Mila Nurhayati; U’ang Abdul Majid (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
Management of new student admissions is made as a method of recruiting students in educational institutions, recruiting new students in the process using a management system. Management is used as a basic concept in the implementation of new student admissions at the State High School 1 Parigi. The method in this study uses a descriptive qualitative approach, the data collection method uses a system of interviews, observations, and documentation. The role of management in the acceptance of new students helps in setting the concept and the flow of implementation of the acceptance of new students. The basic concept of management which consists of planning, organizing, actuating, and controlling, in the implementation of new student admissions, becomes a regulatory center in the stages contained in the management function. The stages regulated by the management function in the admission of new students are contained in the scheme for the admission of new students at the State Senior High School 1 Parigi. The scheme for accepting new students with categories of academic and non-academic achievements, is based on the management function in its implementation